(untitled) (The Research of Medical Science Review, 2025)
This study aims to understand the prevalence of low back and neck pain in dental practitioners and to identify that how dentists can access ergonomic consultations in Khost Afghanistan. Qualitative research method is used in this study. Both primary and secondary data is collected. Primary data is collected through questionnaires shared in the shape of Google Forms and for the literature review the secondary data is collected from books, academic journals and reports. Convenience sampling technique is used for selecting the dentists working in Khost province. The collected data shows that 41.2% had both pains at the same time while 39.7% of the population had only back pain. This pain had many risk factors such as professional, environmental and ergonomic factors. This study also shows that a lot of dentists work more and work without any ergonomic consultation due to unusual posture and insufficient breaks between each patient lack of relaxation during breaks and lack of exercise in daily activity. Also, we can see no exciting ergonomic rules and no implementation of occupational health programs that cause pain.